Cefalometría en rehabilitación - Cortés-C., Nelson; Robledo-P., Mario Francisco; Cuartas-E., María Elena; Giraldo-R., Olga Lucía; Vélez-T., María Teresa (Revista Facultad de Odontología Universidad de Antioquia, 2015)
-